2018
DOI: 10.1590/s1679-45082018ao4146
|View full text |Cite
|
Sign up to set email alerts
|

Types and frequency of errors in the preparation and administration of drugs

Abstract: Objective:To identify compatibility, types and frequency of errors in preparation and administration of intravenous drugs.Methods:A cross-sectional and descriptive study performed at the emergency department of a university hospital in the city of São Paulo (SP). The sample consisted of 303 observations of the preparation and administration of intravenous drugs by nursing aides, nursing technicians and registered nurses, using a systematized script, similar to a checklist. The following variables were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 11 publications
0
54
0
29
Order By: Relevance
“…For nursing technicians and assistants, the variables related to direct assistance to the user obtained the highest factor loadings. This means that these workers are more prone to illness and care errors due to their high workload (14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…For nursing technicians and assistants, the variables related to direct assistance to the user obtained the highest factor loadings. This means that these workers are more prone to illness and care errors due to their high workload (14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…Risk minimization in coadministration of injectable drugs remains important because polymedication is common practice in various patient groups like cancer patients, transplant patients and intensive care patients (neonatal, paediatric, adult). In recent reports, rates of compatibility varied from 9 to 42 % and of incompatibilities from 15 to 68 % [20][21][22][23][24]. Hospital pharmacists should not only answer questions regarding drug-drug compatibilities, but develop together with physicians and nurses incompatibility-reducing infusion schemes to be used in vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies performed in adult patients exposed to multiple IV drugs have found incompatible combinations in 12% to 56%. 19,20 However, these differences can be explained using different references and methods. Contrary to other similar studies, we did not exclude any drugs or infusions (i.e., we collected data of all continuous infusions, including electrolytes, PN, and blood products).…”
Section: Discussionmentioning
confidence: 99%